Efficiency in Kinesiology: Innovative Approaches in Enhancing Motor Skills for Athletic Performance - Minciacchi, Diego (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue dives into the evolving realm of sports science by exploring innovative methods to enhance athletes' motor skills and performance. It showcases research studies aiming to discover validated strategies, cutting-edge approaches, and the intricate interplay of factors that shape athletic excellence. From training methodologies to technological advancements, this collection of empirical investigations and reviews offers valuable insights for both trainers and scientists. We invite readers to join us in uncovering the science behind peak athletic achievement.